1979
DOI: 10.1111/j.1748-5827.1979.tb07023.x
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of Syrian hamsters and other small animals as reservoirs of lymphocytic choriomeningitis virus

Abstract: The history of human infections with lymphocytic choriomeningitis virus is briefly reviewed, with special reference to those of recent years associated with pet Syrian hamsters. Many human infections have been too trivial to have come to the attention of a physician but others have required long periods of convalescence. There is also evidence that foetal damage has arisen from infection during pregnancy. The virus is perpetuated by vertical transmission in those colonies of wild house mice which are tolerantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

1980
1980
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
(29 reference statements)
0
18
0
1
Order By: Relevance
“…Hamsters and guinea pigs may also become infected after close contact with infected M. musculus mice and may also be asymptomatic (16). LCMV transmission in natural rodent hosts occurs vertically, horizontally, and during sexual intercourse.…”
mentioning
confidence: 99%
“…Hamsters and guinea pigs may also become infected after close contact with infected M. musculus mice and may also be asymptomatic (16). LCMV transmission in natural rodent hosts occurs vertically, horizontally, and during sexual intercourse.…”
mentioning
confidence: 99%
“…The systemic distribution of infective WE, as noted for the inbred hamsters (Fig. 4), and as described in prior reports of hamster LCMV infections (Smadel & Wall, 1942;Rhodes & Chapman, 1950;Parker et al, 1976;Skinner & Knight, 1979;Thacker et al, 1982), might suggest that the virus is pantropic. In our study LCMV antigens were found by direct immunofluorescence in most organs examined from hamsters with acute WE infection.…”
Section: Body Weightmentioning
confidence: 77%
“…, and a concern in the epidemiology of human LCMV outbreaks (Ackermann, 1973;Skinner & Knight, 1979). Although hamster LCMV infections were largely regarded as inapparent, benign and immunizing (Smadel & Wall, 1942;Volkert & Hannover Larsen, 1965;Parker et al, 1976), episodes of lethal and non-lethal illness in LCMV-inoculated hamsters have been mentioned in these reports and in other studies (Rhodes & Chapman, 1950;F6rster & WachendSrfer, 1973;Thacker et al, 1982).…”
Section: Lymphocytic Choriomeningitis Virus (Lcmv) Infections Of Syrimentioning
confidence: 88%
“…Les notions d'hôte principal ou secondaire ont d'abord été définies à propos d'autres roboviroses par (ARATA et al 1973, ARATA et GRATZ 1975et BOWEN et al 1997 KNIGHT, 1979), des arénavirus du Nouveau-Monde (ARATA et al, 1973), puis des virus du groupe LASSA KILEY et al, 1986 ;CHILDS et PETERS, 1993 ;BOWEN et al, 1997 ;GONZALEZ et DUPLANTIER, 1999). …”
Section: • Introductionunclassified